The quadrant of doom and hamstring injuries: sexy but too easy? - Buchheit, M.; Avrillon, S.; Simpson, B. M.; Lacome, M.; Guilhem, G. (Sport Performance & Science Reports, 2019)
The different factors relating to hamstrings injury risk have been well reviewed. They include among others age, previous injuries, ethnicity, strength and strength imbalances, exibility, muscle architecture, anatomy, training/competitive load (often high-speed running) and fatigue (1-3). Recently, there has been a growing emphasis on two of those factors, namely hamstring strength and fascicle length (4-7). This is related to the fact that these two muscle properties are modiable factors strongly related to the capacity of the muscle to withstand repeated eccentric contractions during potentially harmful actions such as sprinting. In fact, it has been suggested that players with weak knee exor eccentric strength (as measured using a Nordbord, Vald Performance, Brisbane, Australia) and short biceps femoris long head (BFlh) fascicle length may be at much greater risk of injury than players with strong knee exors and long fascicle length (6). This has led some authors to present the data in the form of a \quadrant of doom" (1), where the overall risk of an individual to sustain an hamstring injury is shown graphically, while plotted as a function of both hamstring strength and fascicle length. It s therefore understood that athletes should escape from the lower left quadrant (high risk), and enter the top right panel of the graph (lower risk), likely via eccentric biased training (1, 8). The idea behind the quadrant is evidence-based and sensible (1), and the highly practical aspect of those strength and structural measures make the approach very appealing for practitioners. Nonetheless, we wished to comment on two important and still overlooked methodological aspects that deserve more attention to make the most of the utilisation of the quadrant: 1) the possible impact of body mass (BM) on Nordbord performance (9-11) 2) the current limitations of the muscle architecture measurements inferred from static ultrasound images and 3) possible differences in individual muscle properties and their relationships with hamstring ability to withstand active lengthening (12, 19).